2011
DOI: 10.4028/www.scientific.net/amr.332-334.1109
|View full text |Cite
|
Sign up to set email alerts
|

Research on Kenaf Degumming with Oxidation Process

Abstract: In this paper, three oxidation processes were employed in kenaf degumming. The properties of degummed fibers such as fineness, residual lignin content were tested, and the degumming effects were analyzed by XRD and IR spectroscopy. The crystallinity of kenaf fiber increased after being treated. The addition of the strong oxidizing agents including potassium peroxymonosulfate and peracetic acid (plan CT2) in the later process of caustic soda and hydrogen peroxide scouring (plan CT1), as well as the usage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Xia et al (2008) investigated the effect of laccase in the linear density of jute fibers, obtaining the result that within 8 h there were no significant changes in linear density. Yan et al (2009) studied the degumming efficiency of laccase-media systems in kenaf fibers and concluded that after 6 h of treatment, the lignin content of kenaf decreased greatly, along with certain improvements in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al (2008) investigated the effect of laccase in the linear density of jute fibers, obtaining the result that within 8 h there were no significant changes in linear density. Yan et al (2009) studied the degumming efficiency of laccase-media systems in kenaf fibers and concluded that after 6 h of treatment, the lignin content of kenaf decreased greatly, along with certain improvements in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%